Faktor Risiko Lingkungan dan Perilaku terhadap Kejadian ISPA pada Anak Usia Balita di Lingkungan Karang Taliwang Timur, Kelurahan Karang Taliwang, Kota Mataram - Kaizar Rafif Adiwangsa; Althaf Rasyid Pradipta (Journal of Applied Health Sciences, 2026)
Acute Respiratory Infection (ARI) is one of the leading causes of morbidity among children under five in Indonesia, particularly in areas with poor environmental conditions and unhealthy behavioral practices. This study aimed to analyze environmental and behavioral risk factors associated with the incidence of ARI among under-five children in Karang Taliwang Timur, Karang Taliwang Subdistrict, Mataram City. This study employed an observational analytic design with a cross-sectional approach. The sample was selected using simple random sampling from the population of children aged 0–59 months. Data were collected through structured questionnaires and direct observation of household environmental conditions, then analyzed using chi-square tests and logistic regression. The results showed significant associations between environmental factors such as ventilation, housing density, humidity, lighting, and indoor smoke exposure with the incidence of ARI (p < 0.05). Behavioral factors including indoor smoking habits, use of traditional cooking fuels, mosquito coil usage, and maternal knowledge were also significantly associated with ARI incidence. Multivariate analysis revealed that house ventilation, exposure to cigarette smoke, and housing density were the most dominant factors influencing ARI among under-five children. In conclusion, ARI incidence among under-five children is influenced by the interaction between environmental and behavioral factors. Therefore, comprehensive interventions focusing on improving household environmental conditions and promoting healthy behaviors are essential to effectively reduce ARI incidence.